Names of hills and terrain elevations in the new toponymic layer of the Warmińsko-Mazurskie Voivodship - Wolnicz-Pawłowska, Ewa (Papers in Linguistics, 2021)
The article refers to Prof. Maria Biolik’s studies on oronymy of the regions of Warmia and Mazury motivated by expressions denoting animals. It is based on toponymy included in Państwowy Rejestr Nazw Geograficznych [Polish National Register of Geographical Names]. The author outlines the oronymy of the Warmińsko-Mazurskie Voivodship, paying special attention to the names of hills motivated by expressions standing for animals. Changes occurring in oronymy reflect civilizational changes. In the past, terrain features useful for farmers and breeders were named, nowadays objects important for inhabitants, tourists, and area administrators are given names. There are fewer toponyms motivated by expressions based on livestock, while the number of oronyms derived from names of wild birds is increasing. This is probably related to the establishment of wildlife reserves in the Warmińsko-Mazurskie Voivodship.